Treatment of advanced thyroid cancer with axitinib: Phase 2 study with pharmacokinetic/pharmacodynamic and quality‐of‐life assessments. Issue 17 (20th May 2014) - Locati, Laura D.; Licitra, Lisa; Agate, Laura; Ou, Sai‐Hong I.; Boucher, Andree; Jarzab, Barbara; Qin, Shukui; Kane, Madeleine A.; Wirth, Lori J.; Chen, Connie; Kim, Sinil; Ingrosso, Antonella; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND In a previous phase 2 trial, axitinib was active and well tolerated in patients with advanced thyroid cancer. In this second phase 2 trial, the efficacy and safety of axitinib were evaluated further in this population, and pharmacokinetic/pharmacodynamic relationships and patient‐reported outcomes were assessed. METHODS Patients (N = 52) with metastatic or unresectable, locally advanced medullary or differentiated thyroid cancer that was refractory or not amenable to iodine‐131 received a starting dose of axitinib 5 mg twice daily. The primary endpoint was the objective response rate (ORR). Secondary endpoints included progression‐free survival (PFS), overall survival (OS), safety, pharmacokinetic parameters, and patient‐reported outcomes assessed with the MD Anderson Symptom Inventory questionnaire. RESULTS The overall ORR was 35% (18 partial responses), and 18 patients had stable disease for ≥16 weeks. The median PFS was 16.1 months, and the median OS was 27.2 months. All‐causality, grade ≥3 adverse events (>5%) were fatigue, dyspnea, diarrhea, decreased weight, pain in extremity, hypertension, decreased appetite, palmar‐plantar erythrodysesthesia, hypocalcemia, and myalgia. Patients who had greater axitinib exposure had a longer median PFS. Quality of life was maintained during treatment with axitinib, and no significant deterioration in symptoms or interference in daily life caused by symptoms, assessed on MD Anderson Symptom Inventory subscales, were observed. CONCLUSIONS Axitinib has activity and a manageable safety profile while maintaining quality of life, and it represents an additional treatment option for patients with advanced thyroid cancer. Cancer 2014;120:2694–2703. © 2014 American Cancer Society.